A decomposition of structural revenue developments for euro area member states - Richard Morris; Lukas Reiss (European Central Bank (ECB), 2020)
This paper presents a framework for analysing the evolution of the structural government deficit estimated using the official EU methodology relevant for the Stability and Growth Pact. The focus of our framework lies in the analysis of the main driving forces of changes in estimated structural government revenue, including the impact of changes to tax legislation, fiscal drag (caused e.g. by the non-indexation of income tax brackets), the composition of economic growth, and a residual. This approach allows us to scrutinise estimates of discretionary revenue measures and fiscal elasticities, both of which play a crucial role in the current EU fiscal governance framework. Between 2010 and 2018, Germany's structural revenue ratio increased substantially even though the estimated impact of changes to tax legislation was close to zero. In most other larger euro area countries, by contrast, structural revenue performed worse than could have been expected based on the estimated impact of discretionary revenue measures. Our approach shows that the composition of economic growth was unfavorable for generating revenue in all analysed countries over this time span. Moreover, in most countries actual revenue grew by less than what could have been expected in view of the discretionary measures taken and developments in the macroeconomic aggregates used to approximate tax bases.
Keywords: H3; H6; E32; E62; 330; cyclical adjustment; fiscal policy; revenue windfalls